Poland Syndrome: A Case Report - Parkash, Satya; Pai, Santosh (Indian Journal of Plastic Surgery, 1983)
A case of Poland's syndrome characterised by anomalies in the shoulder girdle and symbrachydactyly is reported. First web was also involved. Method of correction adopted by us is described.